COMPARISON OF 25 G WHITACRE AND QUINCKE SPINAL NEEDLES FOR INCIDENCE OF POST-DURAL PUNCTURE HEADACHE - MALIK , NA; CHOUGLE , NAK; ALAMGIR , AR; SHAFIQ , S; ISLAM , HFU; FARAZ, A; ASHFAQ, F (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in tertiary care hospital from June 2022 to December 2022 to compare the severity and incidence of PDPH in patients administered spinal anesthesia for lower limb and lower abdominal surgeries using 25G Whitacre and 25G Quincke needles. A sample size of 140 70 in each of the two groups (group Quincke and group Whitacre) was included in the study. Results showed that 11 (15.7%) patients in group Quincke and 1 (1.4%) patient in group Whitacre had PDPH (P=.009). Females had a higher incidence of PDPH (P=0.018). Of 12 patients, 11 had mild, and 1 had moderate PDPH. 11 patients in group Whitacre and 3 in group Quincke had failed spinal anesthesia. 25G Whitacre spinal needles showed lower incidence and severity of post-dural puncture headache than 25G Quincke spinal needles.